Association between maternal - child levels of salivary Mutans Streptococci and early childhood caries - H R Priyadarshini; S S Hiremath; Bennete Fernandes (Dental Research Journal, 2013)
Background: To find out if there is an association between levels of salivary Mutans Streptococci (MS) of mothers and salivary MS and Caries experience of their Children. Materials and Methods: A cross sectional study was designed among 180 mother-child pair attending Vanivilasa Children Hospital, Bangalore, India. Caries was diagnosed using WHO criteria. Ninety children with Early Childhood Caries (ECC) with their mothers were included in case group and 90 caries free children with their mothers were included in the control group. Whole non-stimulated saliva was collected from mothers and children and cultured for MS. Colonies were counted and compared. Data was analyzed using SPSS version 10. Chi-square test and t-test were used to find differences between groups. P value of <0.05 was considered as significant. Results: Among 180 children, 80 of them had a high MS count. Among them, 60 (75%) had ECC and only 20 (25%) were caries free. This difference was significant with P < 0.001. Among 180 mothers, 100 had a high MS count. Among them, 60 (60%) belonged to case group and 40 (40%) to the control group (P = 0.003). Forty nine of the Children in case group with a high count also had mothers with high count as against only 14 in the control group (P < 0.001). Conclusion: Present study showed a strong association between maternal and child salivary MS levels indicating that mother′s MS count could be an important risk indicator for ECC development.